HYDROLYSIS OF NEPTUNIUM(V) AT VARIABLE TEMPERATURES (10-85°C) - Rao L.; Srinivasan T.G.; Garnov A.Y.; Zanonato P.; Di Bernardo P.; Bismondo A. (My University, 2004)
Neptunium is one of the few radioactive elements that are of great concern in the disposal of nuclear wastes in the geological repository, due to its hazards and the long half-life of the isotope, 237Np (t 1/2 = 2.14 × 106 years). To understand and predict the migration behavior of neptunium in the geological media, it is of importance to study its hydrolysis at elevated temperatures, because the temperature in the waste package and the vicinity of the repository could be high. Moreover, the chemical analogy between neptunium(V) and plutonium(V) adds even greater value to this investigation, because the latter could exist at tracer levels in neutral and slightly oxidizing waters but is difficult to study due to its rather labile redox behavior. In this work, the hydrolysis of neptunium(V) was studied at variable temperatures (10 to 85°C) in tetramethylammonium chloride (1.12 mol kg−1). Two hydrolyzed species of neptunium(V), NpO2OH(aq) and NpO2(OH)2 −, were identified by potentiometry and Near-IR absorption spectroscopy. The hydrolysis constants (*β n) and enthalpy of hydrolysis (ΔH n) for the reaction NpO2 + + nH2O = NpO2(OH)n (1−n)+ + nH+ (n = 1 and 2) were determined by titration potentiometry and microcalorimetry. The hydrolysis constants, *β 1 and *β 2, increased by 0.8 and 3.4 orders of magnitude, respectively, as the temperature was increased from 10 to 85°C. The enhancement of hydrolysis at elevated temperatures is mainly due to the significant increase of the degree of ionization of water as the temperature is increased. The hydrolysis reactions are endothermic but become less endothermic as the temperature is increased. The heat capacities of hydrolysis, ΔC p1 and ΔC p2, are calculated to be −(71 ± 17) J K−1 mol−1 and −(127 ± 17) J K−1 mol−1, respectively. Approximation approaches to predict the effect of temperature, including the constant enthalpy approach, the constant heat capacity approach and the DQUANT equation, have been tested with the data.